(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Electronic banking facilitates customer to control their transactions anywhere. Subscribing to the services like mobile banking, allows customer to be updated about their latest account transactions and they don’t need to rush to the bank to get their passbooks updated at the end of financial year. This paper examines online bank channel users preference towards varied channels. The study takes into account the demographic profile of the customers of private sector banks and examines their preference towards diverse banking channels. The channels taken in this study include ATM, Branch banking, Mobile and Internet banking. The study reveals that ATM banking is most preferred and most commonly used banking technology in private sector while Internet banking is most popular.